ISOLATION OF A GOLGI APPARATUS-RICH FRACTION FROM RAT LIVER : I. Method and Morphology - Morré, D. James (The Rockefeller University Press, 1970)
Golgi apparatus were released without fixatives from rat hepatocytes by gentle homogenization, concentrated by differential centrifugation, and purified by sucrose gradient centrifugation. Examination of sections of purified fractions by electron microscopy showed fields of morphologically intact units of Golgi apparatus consisting of stacks of parallel flattened cisternae, secretory vesicles, and small vesicular profiles. Negative staining of unfixed pellets revealed a complex network of anastomotic tubules continuous with platelike structures and secretory vesicles. These structures corresponded, respectively, to the small vesicular profiles and parallel flattened cisternae with attached secretory vesicles of sectioned material. Small fragments of granular endoplasmic reticulum were often closely associated with the peripheral tubules, suggesting sites of continuity in intact hepatocytes.